2020
DOI: 10.1042/bst20190778
|View full text |Cite
|
Sign up to set email alerts
|

PI3K in stemness regulation: from development to cancer

Abstract: The PI3K/AKT pathway is a key target in oncology where most efforts are focussed on phenotypes such as cell proliferation and survival. Comparatively, little attention has been paid to PI3K in stemness regulation, despite the emerging link between acquisition of stem cell-like features and therapeutic failure in cancer. The aim of this review is to summarise current known and unknowns of PI3K-dependent stemness regulation, by integrating knowledge from the fields of developmental, signalling and cancer biology… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 143 publications
(190 reference statements)
0
38
0
1
Order By: Relevance
“…Many growth factors/receptor tyrosine kinases, Ras, and chemokines/GPCRs signal to activate PI3K, which acts through Akt‐dependent and ‐independent mechanisms [119,120]. Treatment of SCC cells with an EGFR inhibitor decreased p63 protein and mRNA levels [121], whilst exogenous EGF increased ΔNp63 and EGFR/HER2 inhibition prevented this induction [62].…”
Section: Signalling Pathways That Regulate P63 Levels or Activitymentioning
confidence: 99%
“…Many growth factors/receptor tyrosine kinases, Ras, and chemokines/GPCRs signal to activate PI3K, which acts through Akt‐dependent and ‐independent mechanisms [119,120]. Treatment of SCC cells with an EGFR inhibitor decreased p63 protein and mRNA levels [121], whilst exogenous EGF increased ΔNp63 and EGFR/HER2 inhibition prevented this induction [62].…”
Section: Signalling Pathways That Regulate P63 Levels or Activitymentioning
confidence: 99%
“…It has been reported that the activation of the PI3K/AKT cascade is a critical step of survival signaling which mediates apoptosis inhibition via multiple mechanisms [ 45 , 46 ]. The PI3K/AKT signaling is a core pathway for stemness acquisition and maintenance in cancer cells [ 47 ]. Furthermore, in lung cancer, the PI3K/AKT pathway was found to be central to cell survival and proliferation and was detected to be constitutively activated [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…PI3K/Akt plays a critical role in regulating cell proliferation, survival, metabolism, and apoptosis of normal cells (Aoki et al, 2017;Tewari et al, 2019). This signaling pathway is abnormally activated in various tumors, e.g., breast, lung, ovarian, and prostate cancers (Lu et al, 2016;Gu et al, 2018;Ediriweera et al, 2019;Verret et al, 2019;Madsen et al, 2020) and participates in mediating tumor MDR (Guerrero-Zotano et al, 2016;Yang et al, 2017;Li et al, 2019a;Liu et al, 2020). For example, PI3K/Akt signaling pathway is involved in paclitaxel resistance when it is abnormally activated in prostate cancer.…”
Section: Discussionmentioning
confidence: 99%